The impact of HIV-related illness on employment. - Yelin, E H (1991)
We used structured telephone interviews to determine the extent of work loss following onset of symptoms, the interval between onset of symptoms and cessation of work, and the risk factors for work loss among 193 persons with symptoms of human immunodeficiency virus (HIV)-related illness attending the AIDS Clinic at the University of California, San Francisco, between October 1, 1988, and September 30, 1989. Estimates of the duration of time between onset of HIV-related symptoms and work loss derive from the life table method of Kaplan and Meier. A Cox proportional hazards model is used to estimate the effect of risk factors on the probability of withdrawing from work in each time interval. Eighty-six percent of the respondents worked prior to onset of the first symptom of HIV-related illness; 40 percent were working at the time of the most recent interview, a mean of 958 days later. The total number of hours worked declined by 59 percent during this time. Kaplan-Meier analysis indicates that 50 percent who worked prior to onset of HIV-related illness stopped working within two years and all had stopped within 10 years after onset of the first symptom.